Reading the Ancestors Message: Semiotics of the Bajang Ratu Temple Ornaments in Mapping Local Wisdom and Majapahit Women - Muktiono, Ayub (Transpublika Publisher, 2025)
Candi Bajang Ratu, a stepped gateway in Trowulan, Mojokerto, is a significant architectural relic from the Majapahit Kingdom (13th-15th centuries CE). The ambiguous gendered name “Bajang Ratu” combining “bajang” (young/small) and “ratu” (a title for women) has prompted interpretations linking the site to influential female figures such as Gayatri Rajapatni. This article aims to uncover the representation of feminine values and local wisdom in the ornamental motifs of Candi Bajang Ratu through a semiotic approach. Employing a qualitative interpretive methodology, the study applies Roland Barthes’ semiotic framework (denotation, connotation, myth) and Charles Sanders Peirce’s triadic signs (icon, index, symbol), integrated within a hermeneutic case study design. Data were collected from secondary sources, including archaeological documentation and academic literature, and analyzed thematically and contextually. The findings reveal that the temple’s ornamental elements, such as hand-like profiles resembling prayer gestures, spiritually sacred spatial symbols, makara reliefs with flowing vines, vegetal motifs, symmetrical arches, fragments of Apsara figures, and the stepped gateway structure, symbolically embody feminine principles: fertility, wisdom, protection, cosmic harmony, flexibility, and adaptability. The curved, flowing architectural forms contrast sharply with masculine aesthetics characterized by rigidity and verticality, affirming the reverence for women not merely as individuals, but as cosmological and moral forces underpinning the kingdom’s continuity. Thus, Candi Bajang Ratu functions as a symbolic monument institutionalizing the recognition of feminine values within Majapahit culture. Far more than a stone structure, it is a symbolic archive of gentle yet enduring power, encapsulating sustainable values that mirror the character of Nusantara women.